PENYELESAIAN ARUS PERALIHAN RANGKAIAN SERI R-L DENGAN TEGANGAN ARUS SEARAH BERBASIS MATLAB - Setyowati, Dwi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2009)
A Case study was taken as a research to investigate the physical process occurred in a simple electric circuit which consists of resistance component R and inductance L with direct voltage source. The general form of series circuit is represented a differential equation of the first order to count the current transfer equation can be found by many methods, they are the first ordered solution, Euler method, the third order Runge-Kutta method, and the fort order Runge-Kutta by using Matlab program. The examinationon by using step measurement with h = 0,05 caused error value to the first order solution method = 2.79%, Euler method = 3.8%, the third order Runge Kutta method = 2.1%, the forth order Runge Kutta method = 2.26%, using step measurement h = 0.1 caused error value to the first order solution = 2.27%, Euler method = 5.23%, the third order Runge Kutta method = 2.27%, the fourth order Runge Kutta method = 1.85% and using step measurement h = 0,15 caused error value to the first order solution = 5.81%, Euler method = 22,35%, the third order Runge Kutta method = 7.19%, the forth order Runge Kutta method = 4.7%.